Supply chain management practices of an automobile manufacturer in Malaysia / Eley Suzana Kasim, Indra Devi Rajamanoharan and Normah Omar - Kasim, Eley Suzana; Rajamanoharan, Indra Devi; Omar, Normah (Universiti Teknologi MARA Cawangan Selangor, 2010)
This preliminary study examines the supply chain management (SCM) practices implemented at an automobile manufacturing firm operating in Malaysia. The case company’s performance measurement system and the accountant’s role in the SCM processes are also examined. The case findings indicate that supply chain planning, long term partnership with suppliers, communication and trust form the basis of effective SCM practices in the selected case company. Contrary to the literature, efforts dedicated to measure and monitor supply chain performance holistically within the case company is still scarce. The findings also suggest that despite the wide use of management accounting tools and practices in SCM processes, accountants’ role in the SCM processes is limited. This initial findings offer some insights on the SCM practices in an automotive manufacturing industry. A next step from this exploratory research could be the development of a framework exploring the impact of SCM practices on organizational performance.